KHOJA AHMAD YASAWIS QUESTION OF THE SPIRITUAL DIVINE PERFECTION OF THE INDIVIDUAL (World Bulletin of Social Sciences, 2022)
The article describes the spiritual-ethical, religious-philosophical content of the mystical views expressed in the wisdom of Khoja Ahmed Yassavi, and the issue of spiritual and divine perfection of a person. According to the teachings of Khoja Ahmad Yassavi, it is important to study the issues of spiritual and divine perfection of a person and to use it practically in the education of a perfect person
Keywords: islam religion; tarikat; sufi heritage; Khoja Ahmad Yasawi